Caracterização dos fatores arqueotafonômicos na fauna de vertebrados do sítio Santana X, Serra de Santana, município de Lagoa Nova – RN – Brasil - Araujo, Jamerson de Medeiros (2019)
The excavations of the Santana X site, located in the county of Lagoa Nova, in the Microrregião da Serra de Santana, in Rio Grande do Norte, have presented a variability of archaeological artifacts, a considerable density of faunal remnants in association with three manchas (dark colored soil in shape of circles) of different dimensions. The faunal remains have aspects that can be related to anthropic manipulation, and with an archeotaphonomic approach applied in zooarchaeological studies, we can establish categories of these faunas, seeking to understand which of these are the result of human actions and which may have been changed from biological or post-depositional process. Archaeological fauna, as part of a whole, are also a representative component of human population of the past, enabling infinite variables in the complex system of interactions and establishments of cultural processes. In this way, the main objective of this research is the characterization of the taphonomic factors susceptible to observation in the archaeological fauna of the Santana X Site, considering its spatial distribution and the particularities of the contexts in each mancha, both in surface and subsurface. The research results indicate different types of recurrent faunas in the site, where they have traits from the three factors, which contribute to the discussion about the variable known as “equifinality”, where two or more distinct alteration patterns can generate a similar result in the archeological record. The dispersion of these materials indicates the formation of faunistic assemblages inserted in each mancha, which leads us to understand that these may be due to specific areas of activities.